Price Discount and Retention of Customers of Pay Television Sector in Ekiti State, Nigeria - Adetayo, Hezekiah Olufemi; Ogundipe, Christie Folake; Olasehinde, Sunday Adeniyi; Omojuwa, Busola Deborah (International Journal of Marketing Research Innovation, 2020)
Aim: To determine the correlation between price discount and customer retention in the Nigerian pay television sector particularly in Ekiti State, Nigeria. Study Design: Descriptive survey research design was used for the study.Place and Duration of Study: Ekiti State, Nigeria between February and November, 2019.Methods: Multi-stage sampling technique was adopted to select the 390 subscribers of pay television in Ekiti State namely Startimes, Dstv and Gotv who are respondents of the study. Primary data used for the study were collected through a well-structured questionnaire and were analysed using percentages, frequency table and multiple regressions.Results: Findings from the study revealed that provision of price discount had a significant positive effect on retention of customers of pay television in Nigeria. Also the study revealed that reduction in subscription fees at interval has a positive effect on customer continuous patronage of the pay television service provider.Conclusion: The study concluded that increased sales promotion led to increased customer retention in the pay television sector in Nigeria. It recommended that pay television service providers should give more of price discounting and free to view stations to customers with a view to attracting potential customers and retaining the existing ones.